Spectral effects and determining the solar spectral distribution for Mugla and Ankara - Murat Kabakci; Rustu Eke (Institute of Advanced Engineering and Science, 2021)
Not only is the theoretical calculation of the amount of solar radiation but also the characteristics of the light so significant in deciding the spectral sensitivity of the PV modules. The amount of radiation reaching on the earth depends on many atmospheric parameters such as wavelength and air mass. Spectral 2 is a model that calculates the amount of radiation for any region depending on the wavelength and atmospheric parameters. There are no theoretical and experimental studies on this subject in Turkey until now. In this study, the amounts of radiation coming to the surface having horizontal and different tilt angles were calculated for Mugla and Ankara. Due to the different climatic characteristics of Mugla and Ankara, the amount of radiation varies. According to the results, in winter and autumn, the amount of radiation which comes to Ankara and Mugla, is different each other. Due to the different climatical and geographical characteristics of Mugla and Ankara, the amount of radiation varies. The model, which is used in this study, due to atmospheric effects that have, is more comprehensive than any other empirical models made in Turkey.